موقف اسرائيل من حرب الخليج العربي الثانية و اثر الحرب على التوجهات العسكرية الاسرائيلية - المبارك، صفاء عبدالوهاب (جامعة البصرة - مركز دراسات البصرة والخليج العربي, 2006)
This study is mainly concerned with Isael’s attitude tward the second Arab Gulf War and the war effect upon Israel military trends. The Israel perspective of U.S. strategy Arab Gulf government. Israel is suspicious of Iraqi military build up .and it considered Iraq as anclear state so it kept its defence association with U.S Israeli interests , also demand a U.S . presence in Iraq . U.S strengthened its relations with, Israel. continued system development , U.S funding of ACES pledge to the Arrow Deploy ability program indate the government officials in Washington and Tel Aviv consider the Arrow to be an important program and Symbol of the strong ties between the U.S and Israel . The Arrow was specifically designed for Israel requirements neutralize tactical ballistic missiles. However the U.S has received numerous lienfits ,especially in the areas of phenomenology and lethality Finally, Israel decided to overthrow Saddam Hussien. Known, also as the ‘American Strategy’ the plan aimed to secure for the U.S apreeminent position in Iraq through a strong military presence
Keywords: اسرائيل -- حرب الخليج الثانية -- العسكرية الاسرائيلية -- دول الخليج العربية -- الاحوال السياسية